DEVELOPMENT OF INTEREST IN YOUTH ENTREPRENEURSHIP IN UTILIZING ORGANIC WASTE INTO SELLING PRODUCT IN THE BORDER AREA - Aloysius Hari Kristianto; Usman - (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The purpose of this research is to find out how to foster entrepreneurial spirit of young people who are involved in waste management. This is deemed necessary because Bengkayang which is still lagging behind are still lacking in the number of people in terms of entrepreneurship and are not familiar with the processing of waste that can be worth selling. The title of this research is Development of Interest In Youth Entrepreneurship In Utilizing Organic Waste Into Selling Product In The Border Area. The productive goods to be produced are compost (liquid and solid). The problem faced is to foster interest in entrepreneurship for Youth in utilizing organic waste into useful selling products and increasing income. Through this research will be carried out the processing of organic waste into compost as a valuable product and see how to foster student interest in creating a sustainable development-based business by managing waste creatively. This type of research is qualitative research with the method used is descriptive method. This method was chosen to be able to objectively describe the management and processing of household-scale organic waste into productive goods that are of selling value. Data collection techniques used were participatory observation techniques and in-depth interview techniques.Keywords: entrepreneurial interest, organic waste, compost fertilizer, products, selling value.